Skin Toxicity in Early Breast Cancer Patients Treated with Field-In-Field Breast Intensity-Modulated Radiotherapy versus Helical Inverse Breast Intensity-Modulated Radiotherapy: Results of a Phase III Randomised Controlled Trial. Issue 1 (January 2021) - Joseph, K.; Vos, L.J.; Gabos, Z.; Pervez, N.; Chafe, S.; Tankel, K.; Warkentin, H.; Ghosh, S.; Amanie, J.; Powell, K.; Polkosnik, L.-A.; Horsman, S.; et al.
Abstract: Aims: Skin toxicity is a common adverse effect of breast radiotherapy. We investigated whether inverse-planned intensity-modulated radiotherapy (IMRT) would reduce the incidence of skin toxicity compared with forward field-in-field breast IMRT (FiF-IMRT) in early stage breast cancer. Materials and methods: This phase III randomised controlled trial compared whole-breast irradiation with either FiF-IMRT or helical tomotherapy IMRT (HT-IMRT), with skin toxicity as the primary end point. Patients received 50 Gy in 25 fractions and were assessed to compare skin toxicity between treatment arms. Results: In total, 177 patients were available for assessment and the median follow-up was 73.1 months. Inverse IMRT achieved more homogeneous coverage than FiF-IMRT; erythema and moist desquamation were higher with FiF-IMRT compared with HT-IMRT (61% versus 34%; P < 0.001; 33% versus 11%; P < 0.001, respectively). Multivariate analysis showed large breast volume, FiF-IMRT and chemotherapy were independent factors associated with worse acute toxicity. There was no difference between treatment arms in the incidence of late toxicities. The 5-year recurrence-free survival was 96.3% for both FiF-IMRT and HT-IMRT and the 5-year overall survival was 96.3% for FiF-IMRT and 97.4% for HT-IMRT. Conclusions: Our study showed significant reduction in acute skin toxicity using HT-IMRT compared with FiF-IMRT, without significant reduction in late skin toxicities. On the basis of these findings, inverse-planned IMRT could be used in routine practice for whole-breast irradiation with careful plan optimisation to achieve the required dose constraints for organs at risk. Highlights: Adjuvant WBI using inverse-planned IMRT in patients with EBC results in significant reduction in acute skin toxicity. Lower acute skin toxicity with inverse-planned IMRT did not translate into reduced late skin fibrosis. Acute skin toxicity correlated with large breast volume, adjuvant chemotherapy and radiotherapy technique (FiF-IMRT). Careful plan optimisation required to generate inverse IMRT plans without exceeding dose limits for OARs.